DIFFERENCES IN STUDENT LEARNING OUTCOMES USING CONCEPT ATTAINMENT MODEL AND ADVANCE ORGANIZER MODEL ON HEXAPODA MATERIAL - Restu Berkat Gea; M Yusuf Nasution (Universitas Negeri Medan, 2022)
The results of studying biology for class X SMA Negeri 18 Medan on Hexapoda are still low. Students still experience difficulties in learning Hexapod material because the material is very complex. This study aims to determine differences in student learning outcomes taught using the concept achievement model and the advance organizer model in Hexapoda material in grade 10. The research population was grade X SMA Negeri 18 Medan which consists of 3 classes namely X-IPA1, X-IPA2 and X-IPA3. Sampling was done by simple random sampling technique. The samples taken were class X-IPA1 as the class taught by the concept achievement model and X-IPA2 as the class taught by the advanced organizer model. This research is a quasy experiment research. The instrument used in measuring learning outcomes in this study was a test in the form of a multiple choice test totaling 20 questions. Hypothesis testing is done by t test with α = 0.05. Before being given treatment, the average pretest value for experimental class I was 51.3 and after being given treatment it was 84 while the average pretest value for experimental class II was 50.96 and after being given treatment it was 79.67. Based on these values, it is known that the average student learning outcomes in the experimental class I was higher than the experimental class II. The hypothesis test shows t-count > t-table, with dk 59, α=0.05 is 2.2670> 2.0009 which means there are differences in student learning outcomes taught using the concept achievement model and the advance organizer model on Hexapoda material.